Analysis of Humic Acid Content in Reject Coal as an Organic Fertilizer in Coal Mining Reclamation Areas - Roy Nastigor Nasution; Edy Nursanto; Rika Ernawati; Shofa Rijalul Haq (Journal of Metallurgical Engineering and Processing Technology, 2024)
An important effort to restore the productivity of degraded land is land reclamation, especially in areas where ecosystems have been destroyed. The use of organic materials that can improve soil quality is one of the methods used in the reclamation process. Humic acid, an organic component found in natural organic materials such as humus and compost, has attracted attention as an organic fertilizer material that can be used in reclamation, the aim of this research is to analyze the use of humic acid as an organic fertilizer in the reclamation process in the Spice Land area, South Kalimantan. This research was carried out through field and laboratory studies, looking at how humic acid affects the properties of degraded soil, pH, height and stem diameter. The results showed that the application of humic acid significantly improved the quality of reclaimed soil by increasing the soil's capacity to store water and increasing its fertility in addition to the physicochemical benefits, the use of humic acid helps the environment. By using it as an organic fertilizer in the reclamation process, you no longer need to use synthetic chemical fertilizers, which can have a bad impact on the environment. It also supports sustainable agricultural practices ,in reclamation, the use of humic acid as an organic fertilizer shows great potential to increase the success rate of restoration of degraded land. Consequently, this research encourages environmentally friendly practices for the restoration of damaged ecosystems and helps sustainable land management.